Relations entre associations féminines palestiniennes des deux côtés de la Ligne verte - Elisabeth Marteu (EchoGéo)
Arab women’s organizations in Israel maintain various relations with their Palestinian counterparts. Based on national solidarities, professional cooperations and/or increasing humanitarian assistance, contacts between Palestinians through the Green Line are in constant reconfiguration. This paper focuses on women’s mobilization in order to highlight transborder relations between Palestinian people from Israel and the Palestinian Territories. By studying links that developped between women’s organizations in the Israeli-Palestinian context, this research aims to understand the reajustement of inter-Palestinian solidarity. The outbreak of the second Intifada in 2000 strengthened Arab citizen’s claim of their Palestinian identity. Nevertheless immediate stakes of their social and political mobilization are anchored in the Israeli state’s boundaries. Similarly, the deterioration of the humanitarian situation in the Palestinian Territories influences the localization of civil organizations’ repertoires of action. Thus, even though some Arab nationalist and Islamic movements stand up for a Palestinian transborder mobilization, realities and local priorities still contain any substantial achievement.